2014
DOI: 10.1590/s1415-43662014000300003
|View full text |Cite
|
Sign up to set email alerts
|

Portable meters for nutritional assessment in plants of gerbera fertigated with electrical conductivity levels

Abstract: A B S T R A C TRapid tests to assess the nutritional status of plants gerbera can make easier the decision of any adjustments in the fertilization of the substrate. The study was conducted to evaluate nutritionally fertigated gerbera plants with increasing levels of electrical conductivity (EC), using portable meters nitrate and potassium, and chlorophyll. For this, two experiments were conducted. A randomized block design with five levels of EC (0.5, 2.0, 3.5, 5.0 and 6.5 dS m -1 ) and four replications was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 11 publications
1
12
1
Order By: Relevance
“…According to Mota et al (2014), pH values for Golden Yellow cultivar, throughout the crop cycle, were slightly higher than the Cherry cultivar, unlike the observed behavior for EC values, as they were low. The authors found that, the lower applied solution concentration, higher the pH, proving the positive inclusion of low EC on the development of plants.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…According to Mota et al (2014), pH values for Golden Yellow cultivar, throughout the crop cycle, were slightly higher than the Cherry cultivar, unlike the observed behavior for EC values, as they were low. The authors found that, the lower applied solution concentration, higher the pH, proving the positive inclusion of low EC on the development of plants.…”
Section: Resultsmentioning
confidence: 58%
“…This fact is related to lower pH, as well as the other treatments had higher pH and reduced EC. Ludwig et al (2014), Mota et al (2014), and Ludwig et al (2015) prove this fact. Means followed by the same letter in the column do not differ by Tukey's test at 5% significance level.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Gerbera (Gerbera jamesoni) is commercially cultivated as a cut flower or in pots, and has high acceptance in the market of flowers and ornamental plants in Brazil, for presenting flowers with great diversity of colors, good durability and resistance to transportation (MOTA et al, 2014;LUDWIG et al, 2015;SANTOS et al, 2017). In the cultivation of potted gerbera, it is important to look for a high number of flower stems; inflorescences with large diameter; small size; and adequate leaf branching, to form a balanced set between the vegetative and reproductive part (LUDWIG et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…An adequate fertilization, both mineral and organic, favors the production and quality of flowers and, with the expansion of the commercial production of flowers and ornamental plants in Brazil, there is a need for more studies on fertilization for this group of plants (LUDWIG et al, 2008;MOTA et al, 2014;SANTOS et al, 2015;SANTOS et al, 2017). In addition, in Brazil, it is common for farmers to manage fertilization empirically, supplying large amounts of nutrients, which are often not required by plants, without following agronomic criteria (LUDWIG et al, 2010;GUERRERO et al, 2013).…”
Section: Introductionmentioning
confidence: 99%